#FREE LUIGI BETWEEN PLAYFUL RESISTANCE AND RUPTURE - Stewart, Michelle Robin; Laperle, Samuel (AoIR Selected Papers of Internet Research, 2026)
On December 4th, 2024, Brian Thompson, CEO of UnitedHealthcare was killed in New York City. The shooting quickly galvanized public critiques of the American healthcare system. Our proposal focuses upon user-generated content featuring Luigi Mangione, the 26-year-old suspect, arrested days later. Indeed, the lionization of Mangione across popular social media platforms signalled social rupture of internet practices, of generational allegiances, and of class consciousness. We address the multiple meanings attributed to Mangione’s act and explore the extent to which the case marks complex cultural and political realignments. We use mixed methods to analyze all available posts and comments linked to the Mangione case that emerged on TikTok immediately following the shooting. With attention to platform affordances and online subcultural practices, we explore content that is political, transgressive and ambiguous at once. We draw upon a variety of sources to theorize and update our understanding of the tactics of resistance available to the dispossessed, drawing on cultural historian James Scott’s notion of “weapons of the weak” and exploring it in relation to recent studies of political communication on TikTok. As a final line of questioning regarding social rupture, we examine the often-contradictory objectives of users and the social media monopolies that manage platforms.